2011
DOI: 10.1038/ng.939
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genome-wide association studies in east Asians identify new genetic loci influencing metabolic traits

Abstract: l e t t e r sTo identify the genetic bases for nine metabolic traits, we conducted a meta-analysis combining Korean genome-wide association results from the KARE project (n = 8,842) and the HEXA shared control study (n = 3,703). We verified the associations of the loci selected from the discovery metaanalysis in the replication stage (30,395 individuals from the BioBank Japan genome-wide association study and individuals comprising the Health2 and Shanghai Jiao Tong University Diabetes cohorts). We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
260
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 262 publications
(275 citation statements)
references
References 42 publications
14
260
1
Order By: Relevance
“…The enrichment of markers for the 11q23.3 region (114,600,001-121,300,000 bp as GRCh38) by imputation increased the number of SNPs or single nucleotide variants previous studies have indicated multiple independent susceptibility loci of hypertriglyceridemia ( 13,14 ), and to examine the possibility of the existence of more than one causal variant in this region .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enrichment of markers for the 11q23.3 region (114,600,001-121,300,000 bp as GRCh38) by imputation increased the number of SNPs or single nucleotide variants previous studies have indicated multiple independent susceptibility loci of hypertriglyceridemia ( 13,14 ), and to examine the possibility of the existence of more than one causal variant in this region .…”
Section: Resultsmentioning
confidence: 99%
“…Serum TG level was measured using standard enzymatic method in a centralized laboratory. Details of the KARE are described in previous reports ( 13,15 ). The genome-wide genetic marker information was available for a total of 8,842 individuals.…”
Section: Subjectsmentioning
confidence: 99%
“…A recent GWAS performed in East Asians for metabolic traits identified one single-nucleotide polymorphism (SNP), GCKR rs780092 (T-allele), to be associated with higher TG concentrations at the genome-wide significance level [10]. SNP rs780092 was moderately in linkage disequilibrium (LD) with the former identified variants in whites, rs780094 (r 2 =0.50) and rs1260326 (r 2 =0.42) in East Asians.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP imputation was performed using the IMPUTE program, 11 and the detailed imputation procedure has been published. 12 The International HapMap data from 90 individuals from the JPT and HCB populations were used as a reference panel, 13 with the reference sample size of 90 individuals having more than 95% imputation accuracy. 14 The effect of genotype was computed by linear regression analysis.…”
mentioning
confidence: 99%